Tensile and fatigue behaviour of as-forged AZ31B extrusion (Fracture and Structural Integrity, 2016)
Tensile and stress controlled fatigue tests were performed to investigate the influence of forging at a temperature of 400°C at different rates, on the performance of extruded AZ31B magnesium alloy. The obtained microstructural analysis showed that the extruded AZ31B magnesium alloy possesses a bimodal grain structure with strong basal texture. In contrast, the forged samples showed refined grains and a weaker texture. During tensile testing, a maximum yield and ultimate tensile strength of about 163 MPa and 268 MPa were obtained for the forged samples showing an increase of 102% and 7%, respectively from the as-extruded material. At the same time, a significant improvement of fatigue life was also observed for the sample forged at the rate of 100 mm/min. The fractographic analysis of the fracture surfaces showed that ductile type fractures occurred in both as-extruded and forged samples. However, more dimples and plastic deformation were identified in the fracture surfaces of the forged specimens. It is believed that forging improved the fatigue life by a combination of grain refinement and texture modification resulting in improved yield and ductility. KEYWORDS. AZ31B; Forging; Fatigue Characterization; Fracture; Texture.
Keywords: AZ31B; Forging; Fatigue Characterization; Fracture; Texture